Le Laboratoire de prévention de la criminalité de l’Université de Lausanne : une approche par projets favorisant l’expérience d’apprentissage des étudiants - Manon Jendly; Stéphanie Loup; Romain Voisard; Denis Berthiaume; Jean-Moïse Rochat; Emmanuel Sylvestre (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This article discusses a pedagogical experience that aims to facilitate master students’ engagement in dealing with real issues related to crime prevention, to develop their relationships with practitioners and, ultimately, to enhance their employability in this field. The crime prevention laboratory implies the realization of a project through a participative learning approach, which places the students in a direct relationship with reality by bringing them to confront their theoretical knowledge with a real case, submitted by an external partner of the university. We present the educational outcomes of this experience, but also the challenges in terms of knowledge and problem solving, group dynamics and dialectics between the university and the professional world.